When ESG Meets Cybersecurity: The Moderating Effect of Digital Protection on Bank Performance in MENAT Countries - Benthabet, Safa (International Journal of Economics and Financial Issues, 2025)
This study advances sustainable finance literature by examining how financial institutions can enhance resilience through strategic integration of ESG principles and cyber-security policies. Using a sample of 35 banks from the Middle East, North Africa, and Türkiye (MENAT) region (2015-2023), we employ both static and dynamic panel estimators to analyze: (1) the direct relationship between ESG performance and financial metrics (ROA, ROE, MV), and (2) the moderating effect of cybersecurity policies on this relationship. Our results demonstrate that robust ESG performance significantly improves all financial measures, particularly ROA. The moderation analysis reveals that cybersecurity policies significantly enhance ESG’s positive impact on profitability, despite initial implementation costs. These findings have three significant contributions: First, it provides novel empirical evidence from the under-researched MENAT context. Second, it pioneers the methodological approach of testing cybersecurity as an institutional-level moderator in the ESG-performance nexus. Third, it demonstrates how integrated sustainability-digital governance frameworks create value. These findings guide bank executives and regulators in developing coordinated ESG-cybersecurity investment strategies for emerging markets.